2015
DOI: 10.1007/s10661-015-4319-7
|View full text |Cite
|
Sign up to set email alerts
|

Toxic elements in groundwater of Lagos and Ogun States, Southwest, Nigeria and their human health risk assessment

Abstract: A good quality drinking water is essential for human survival. However, a large percentage of the populations in most developing countries (Nigeria inclusive) do not have access to potable water. This study was therefore conducted to assess the extent of risk arising from consumption of toxic elements in groundwater samples collected from Lagos and Ogun States, Southwest, Nigeria. Twelve toxic elements concentrations (As, Mn, Cd, Cr, Pb, Ni, Al, Ti, V, Hg, Li, and Sn) were determined from 170 groundwater sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 39 publications
1
16
0
2
Order By: Relevance
“…Studies performed in Pakistan indicate that more than 74 million inhabitants are subjected to health risk from As, Cd, Cr, Fe, Mn, Ni, and Pb contamination of groundwater (Bhowmik et al 2015). Similarly, other studies carried out in highly populated states of Nigeria (more than 16 million inhabitants) suggest a high risk of cancer development due to the ingestion of groundwater with elevated levels of Cr, Pb, As, and Cd (Ayedun et al 2015). In addition, studies carried out by the US Geological Survey in public-supply wells distributed across 35 states of the USA indicated that the chemical mixtures in groundwater that had the greatest potential toxicity were primarily composed of trace elements (including As, Sr, and U) (Toccalino et al 2012).…”
Section: Introductionmentioning
confidence: 73%
“…Studies performed in Pakistan indicate that more than 74 million inhabitants are subjected to health risk from As, Cd, Cr, Fe, Mn, Ni, and Pb contamination of groundwater (Bhowmik et al 2015). Similarly, other studies carried out in highly populated states of Nigeria (more than 16 million inhabitants) suggest a high risk of cancer development due to the ingestion of groundwater with elevated levels of Cr, Pb, As, and Cd (Ayedun et al 2015). In addition, studies carried out by the US Geological Survey in public-supply wells distributed across 35 states of the USA indicated that the chemical mixtures in groundwater that had the greatest potential toxicity were primarily composed of trace elements (including As, Sr, and U) (Toccalino et al 2012).…”
Section: Introductionmentioning
confidence: 73%
“…), IR = Ingestion rate of water or fish; water = 2 L day −1 for an adult, 1 L day −1 for a child, 0.75 L day −1 for an infant (Ayedun et al 2015); Fish = 24.7 g day −1 for an adult based on the Food and Agriculture Organization (FAO) annual per capita fish consumption statistics for Nigeria given as 9.0 kg (FAO 2008). C = Concentration of trace metals in water (μg L −1 ) or fish (μg kg −1 ) samples, BW = Body weight (kg); 60 kg for an adult, 10 kg for a child, 5 kg for an infant (Ayantobo et al 2014a).…”
Section: Health Risk Assessmentmentioning
confidence: 99%
“…Drinking water contamination by different microorganisms such as coliforms (Kumpel et al, 2016), Staphylococcus aureus and Pseudomonas species (Igbeneghu and Lamikanra, 2014) have been reported in Nigeria. Also, the presence of metals like iron, calcium, chromium and aluminum have been found in surface water (Titilawo et al, 2018) and sachet-packed water (Emenike et al, 2018), including cadmium, lead, manganese and nickel in groundwater (Ayedun et al, 2015) above permissible levels for drinking water. Other contaminants such as fluoride (Emenike et al, 2018) and light polycyclic aromatic hydrocarbons have also been reported to be present in groundwater in levels above permissible limits in some locations in Nigeria (Adekunle et al, 2017).…”
Section: Introductionmentioning
confidence: 99%